Beck, Rose Marie & Frank Wittmann (eds.) 2004. African Media Cultures – Transdisciplinary Perspectives. Cultures de médias en Afrique. Perspectives transdisciplinaires - Topics in African Studies, Vol. 2, Köln: Köppe Verlag, 320 pages, 2 b/w photos, 17 tables, 15 graphs, €34,80 - Pasch, Helma (AAeO - Afrikanistik-Aegyptologie-Online, 2006)
Beck and Wittmann's volume is a most welcome contribution about types and uses of traditional and modern media in Africa. Their volume is divided into fifteen chapters preceded by a comprehensive introduction and followed by some information about the authors